Surface-Sensitive Microwear Texture Analysis of Attrition and Erosion. (March 2017) - Ranjitkar, S.; Turan, A.; Mann, C.; Gully, G.A.; Marsman, M.; Edwards, S.; Kaidonis, J.A.; Hall, C.; Lekkas, D.; Wetselaar, P.; Brook, A.H.; Lobbezoo, F.; et al.
Scale-sensitive fractal analysis of high-resolution 3-dimensional surface reconstructions of wear patterns has advanced our knowledge in evolutionary biology, and has opened up opportunities for translatory applications in clinical practice. To elucidate the microwear characteristics of attrition and erosion in worn natural teeth, we scanned 50 extracted human teeth using a confocal profiler at a high optical resolution (X–Y, 0.17 µm; Z < 3 nm). Our hypothesis was that microwear complexity would be greater in erosion and that anisotropy would be greater in attrition. The teeth were divided into 4 groups, including 2 wear types (attrition and erosion) and 2 locations (anterior and posterior teeth; n = 12 for each anterior group, n = 13 for each posterior group) for 2 tissue types (enamel and dentine). The raw 3-dimensional data cloud was subjected to a newly developed rigorous standardization technique to reduce interscanner variability as well as to filter anomalous scanning data. Linear mixed effects (regression) analyses conducted separately for the dependent variables, complexity and anisotropy, showed the following effects of the independent variables: significant interactions between wear type and tissue type ( P = 0.0157 and P = 0.0003, respectively) and significant effects of location ( P < 0.0001 and P = 0.0035, respectively). There were significant associations between complexity and anisotropy when the dependent variable was either complexity ( P = 0.0003) or anisotropy ( P = 0.0014). Our findings of greater complexity in erosion and greater anisotropy in attrition confirm our hypothesis. The greatest geometric means were noted in dentine erosion for complexity and dentine attrition for anisotropy. Dentine also exhibited microwear characteristics that were more consistent with wear types than enamel. Overall, our findings could complement macrowear assessment in dental clinical practice and research and could assist in the early detection and management of pathologic tooth wear.